Use of Organic Acid, Herbs and Their Combination to Improve the Utilization of Commercial Low Protein Broiler Diets - El-Hakim, A.S. Abd; Cherian, G.; Ali, M.N. (International Journal of Poultry Science, 2008)
Two experiments were conducted to investigate the growth performance, carcass characteristics, organ weights, plasma proteins and fecal N excretion in broilers fed a 18% crude protein diet supplemented with Thymus vulgaris, Curcuma longa, citric acid, lactic acid or their combinations. In the first experiment, 98 broiler chicks were fed a control diet or a control diet with 0.2% Thyme (TH), 0.2% Curcuma longa (CL), 0.2% Citric acid (CIT), 0.2% TH + 0.2% CL, 0.2% TH + 0.2% CIT, 0.2% CL + 0.2% CIT. In the second experiment, 98 broiler chicks were fed a control diet with 0.2% TH, 0.2% lactic acid (LAC), 0.2% CIT, 0.2% TH + 0.2% LAC, 0.2% TH + 0.2% CIT, 0.1% LAC + 0.1% CIT. Addition of 0.2% TH, or TH + CIT increased weight gain in 21 day-old birds in experiment 1 (p